A Comparative Cyclic Voltametric Study on Rare Earth (Eu, Sm, Dy, and Tb) Ions Doped La10Si6O27 Nanophosphors for Sensor Application. (23rd September 2022) - Kumar, A. Naveen; Jnaneshwara, D.M.; Ravikumar, C.R.; Murthy, H.C. Ananda; Prashantha, S.C.; Kumar, M.R. Anil; Ajay, K.M.
Abstract : The rare earth (RE = Eu, Sm, Dy, and Tb) ions doped La10 Si6 O27 nanophosphor was synthesized by a simple solution combustion method. The prepared La10 Si6 O27 :RE 3+ nanophosphors (LNPs) were subjected to diverse technical tools for exploring their structural, optical, morphological, and electrochemical features. The structural analysis using powder X-ray diffraction (PXRD) patterns revealed the hexagonal oxy apatite phase for LNPs with a crystallite size in the range of 25–50 nm, and the equivalent was affirmed by image analysis via transmission electron microscopy (TEM). Utilizing DRS data, the bandgap energy (Eg) values were recorded for LNPs. Cyclic voltametric (CV), electrochemical impedance spectroscopy (EIS), and sensor studies were performed using a modified carbon paste electrode of LNPs. The modified LNP electrodes were found to be highly effective in sensing paracetamol in acidic medium with a quick response time of 3 secs for sensing the drugs at 1 mM concentration. All the RE ions Eu 3+, Sm 3+, Dy 3+, and Tb 3+ (5 mol%)-doped LNPs exhibited the most promising electrochemical sensing characteristics.